Electrode and secondary battery including the same

By using carbon nanotube structures and point-type conductive agents in the electrode active material layer of lithium secondary batteries, the problem of damage to the conductive network during charging and discharging is solved. The energy density and life characteristics of the battery have been improved.

CN119447298APending Publication Date: 2025-02-14LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411510596.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-10-04
Filing Date
2020-09-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The conductive network of existing lithium secondary batteries is easily damaged during charging and discharging, resulting in a decrease in the energy density and life characteristics of the battery, and the content of conductive agent is high, affecting the overall performance of the battery.

Method used

Using an electrode active material layer including 2 to 5,000 single-wall carbon nanotube units side by side and point-type conductive agent, the integrity of the conductive network is maintained through the length of the carbon nanotube structure and the network structure, and through Point-type conductive agents form a short conductive network, improving the conductivity and energy density of the battery.

Benefits of technology

It effectively reduces the internal resistance of the battery, improves the energy density, output characteristics and life characteristics of the battery, and reduces the content of conductive agents, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447298A_ABST
    Figure CN119447298A_ABST
Patent Text Reader

Abstract

The present invention relates to an electrode and a secondary battery comprising the same, the electrode comprising an electrode active material layer, the electrode active material layer comprising an electrode active material and a conductive agent, the conductive agent comprising: a dot-type conductive agent; and a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are arranged side by side and bonded to each other, in which the average length of the carbon nanotube structure is 1 [mu] m to 500 [mu] m.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application with an application date of September 28, 2020, application number 202080049069.7, and invention name “Electrode and secondary battery comprising the electrode” (PCT / KR2020 / 013286, date of entry into the national phase on January 4, 2022).

[0002] CROSS-REFERENCE TO RELATED APPLICATIONS

[0003] This application claims the benefit of priority to Korean Patent Application No. 10-2019-0123301, filed on October 4, 2019, the disclosure of which is incorporated herein by reference in its entirety. Technical Field

[0004] The present invention relates to an electrode and a secondary battery including the electrode, the electrode including an electrode active material layer, the electrode active material layer including an electrode active material and a conductive agent, the conductive agent including: a point-type conductive agent; and a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other, wherein the average length of the carbon nanotube structure is 1 μm to 500 μm, and the carbon nanotube structure is included in the electrode active material layer in an amount of 0.01 wt % to 5.0 wt %. Background Art

[0005] With the recent technological development and increased demand for mobile devices, the demand for batteries as energy sources has increased significantly, and thus various studies on batteries that can meet various needs have been carried out. In particular, as a power source for such devices, lithium secondary batteries with excellent life characteristics and cycle characteristics and high energy density have been actively studied.

[0006] A lithium secondary battery refers to a battery that includes a non-aqueous electrolyte containing lithium ions in a positive electrode assembly, wherein the electrode assembly includes: a positive electrode including a positive electrode active material capable of inserting / deinserting lithium ions, a negative electrode including a negative electrode active material capable of inserting / deinserting lithium ions, and a microporous separator disposed between the positive electrode and the negative electrode.

[0007] At the same time, since the conductivity of the electrode cannot be ensured only by the electrode active material such as the positive electrode active material or the negative electrode active material, the resistance of the battery may be too high, and therefore, the electrode generally further includes a conductive agent. Generally, a point-type conductive agent such as carbon black is mainly used, and a linear conductive agent such as carbon nanotubes and carbon nanofibers has also been used to increase the battery capacity by further improving the conductivity.

[0008] Single-walled carbon nanotubes are one of the linear conductive agents, and due to their thin and elongated shape, the conductivity in the electrode active material layer is improved. Therefore, in general, the single-walled carbon nanotubes are completely dispersed to prepare a dispersion including single-walled carbon nanotube units, wherein the single-walled carbon nanotube units exist in a single chain form, and then the electrode slurry is prepared by the dispersion, and the electrode active material layer is prepared by the electrode slurry. Therefore, the single-walled carbon nanotube exists in the electrode active material layer as a unit (single chain). However, when the battery is repeatedly charged and discharged, the surface of the single-walled carbon nanotube unit is damaged or the single-walled carbon nanotube unit is broken (the final length is 1-3 μm), and therefore, there is a limitation that it is difficult to maintain a conductive network in the electrode active material layer. Therefore, the conductive network is blocked or reduced, and this reduces the energy density and life characteristics of the battery and increases the resistance of the battery.

[0009] For this purpose, there is a method of using multi-walled carbon nanotubes to ensure conductivity when the carbon nanotube surface is damaged. However, due to the structure formed by node growth, the multi-walled carbon nanotubes are cut into too short lengths during the preparation of the dispersion, so there is a limitation in improving the conductivity of the electrode.

[0010] Therefore, there is a need for a method that can introduce a new form of conductive agent to reduce the resistance of the electrode, improve the life characteristics of the battery, and reduce the content of the conductive agent to increase the energy density of the battery. Summary of the invention

[0011] Technical issues

[0012] One aspect of the present invention provides an electrode capable of reducing the internal resistance of a battery and capable of improving the energy density, output characteristics, and life characteristics of the battery

[0013] Another aspect of the present invention provides a secondary battery including the electrode.

[0014] Technical Solution

[0015] According to one aspect of the present invention, there is provided an electrode comprising an electrode active material layer, the electrode active material layer comprising an electrode active material and a conductive agent, the conductive agent comprising: a point-type conductive agent; and a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other, wherein the average length of the carbon nanotube structure is 1 μm to 500 μm, and the carbon nanotube structure is included in the electrode active material layer in an amount of 0.01 wt % to 5.0 wt %.

[0016] According to another aspect of the present invention, a secondary battery including the electrode is provided.

[0017] Beneficial Effects

[0018] The electrode according to the present invention includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other, and thus a conductive network can be smoothly maintained even during the charging and discharging process of the battery. Therefore, the resistance of the electrode can be kept at a low level, the energy density and life characteristics of the battery can be improved, and the resistance of the battery can be reduced. In addition, since the carbon nanotube structure is present in the electrode in the form of a long rope, even if the battery is continuously charged and discharged, the conductivity decrease caused by the damage of the carbon nanotube structure can be suppressed, and a long conductive network can be formed. In addition, since the point-type conductive agent included in the electrode helps to form a short conductive network, the conductive network can be uniformly formed on the entire electrode due to the combined use of the point-type conductive agent and the carbon nanotube. Therefore, the life characteristics of the battery can be further improved, and the content of the conductive agent can be reduced to increase the energy density of the battery and further reduce the resistance of the battery. In addition, the point-type conductive agent can disperse the electrons in the electrode throughout the electrode, thereby suppressing the ignition caused by the phenomenon that the electrons are confined to the carbon nanotube structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 These are SEM photographs of the multi-walled carbon nanotube unit (A) used in the comparative example and the carbon nanotube structure (B and C) used in the examples of the present invention.

[0020] Figure 2 These are TEM photographs of the carbon nanotube structure (A) used in the example of the present invention and the single-walled carbon nanotube unit (B) used in the comparative example.

[0021] Figure 3 This is a SEM photograph of the electrode in Example 1 of the present invention.

[0022] Figure 4 This is a SEM photograph of the electrode in Comparative Example 1 of the present invention.

[0023] Figure 5 This is a SEM photograph of the electrode in Comparative Example 2 of the present invention.

[0024] Figure 6 This is a SEM photograph of the electrode in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0025] The terms or words used in the specification and the claims should not be construed as being limited to the ordinary meaning or dictionary meaning, but should be construed as meanings and concepts consistent with the technical spirit based on the principle that the inventor can appropriately define the concept of the terms in order to interpret the present invention in the best manner.

[0026] The terminology used herein is for the purpose of describing particular exemplary embodiments only and is not intended to be limiting of the present invention. Terms in the singular may include plural forms unless the context clearly indicates otherwise.

[0027] It will be understood that when used in this specification, the terms "comprises", "comprising" or "having" specify the presence of stated features, numbers, steps, elements or combinations thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, elements or combinations thereof.

[0028] In the present specification, the expression "specific surface area" is measured by the BET method, wherein, in particular, the specific surface area can be calculated from the nitrogen adsorption amount at liquid nitrogen temperature (77K) using BELSORP-mini II manufactured by Bell Japan.

[0029] In this specification, the average particle size (D 50 ) can be defined as the particle size at which the cumulative volume in the particle size distribution curve is 50%. For example, the average particle size (D 50 ). Laser diffraction is generally capable of measuring particle sizes ranging from submicron to several millimeters, and can obtain results with high repeatability and high resolution.

[0030] In the present invention, a single-walled carbon nanotube unit refers to a tubular unit having a single wall composed of carbon atoms, and a multi-walled carbon nanotube unit refers to a tubular unit having multiple walls composed of carbon atoms in one tube.

[0031] Hereinafter, the present invention will be described in detail.

[0032] electrode

[0033] An electrode includes an electrode active material layer according to one aspect of the present invention, the electrode active material layer includes an electrode active material and a conductive agent, the conductive agent including: a point-type conductive agent; and a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other, wherein the average length of the carbon nanotube structure is 1 μm to 500 μm, and the carbon nanotube structure is included in the electrode active material layer in an amount of 0.01 wt % to 5.0 wt %.

[0034] The electrode can be a positive electrode or a negative electrode. The electrode may include an electrode active material layer, and the electrode active material layer may include an electrode active material. When the electrode is a positive electrode, the electrode active material layer included in the positive electrode is a positive electrode active material layer, and the electrode active material of the positive electrode active material layer is a positive electrode active material. When the electrode is a negative electrode, the electrode active material layer included in the negative electrode is a negative electrode active material layer, and the electrode active material of the negative electrode is referred to as a negative electrode active material.

[0035] The positive electrode may include a positive electrode active material layer. The positive electrode may further include a positive electrode current collector, and in this case, the positive electrode active material layer may be disposed on one surface or both surfaces of the positive electrode current collector.

[0036] There is no particular limitation on the positive electrode current collector as long as the material of the positive electrode current collector has conductivity and does not cause adverse chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, their alloys, these materials surface-treated with carbon, nickel, titanium, silver or the like, calcined carbon, etc. can be used.

[0037] The positive electrode current collector generally may have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the positive electrode current collector to improve the adhesion of the positive electrode active material. In addition, the positive electrode current collector can be used in various shapes such as films, sheets, foils, meshes, porous bodies, foams, non-woven fabric bodies, etc.

[0038] The positive electrode active material layer may include a positive electrode active material and a conductive agent.

[0039] The positive electrode active material can be a positive electrode active material commonly used in the art, and there is no particular limitation on its type.

[0040] For example, at least one metal-containing lithium oxide such as cobalt, manganese, nickel or aluminum can be used as the positive electrode active material. More particularly, the lithium oxide may include: lithium manganese-based oxides (such as LiMnO2, LiMn2O, etc.); lithium cobalt-based oxides (such as LiCoO2, etc.); lithium nickel-based oxides (such as LiNiO2, etc.); lithium nickel manganese-based oxides (such as LiNi 1-Y1 Mn Y1 O2 (where 0 < Y1 < 1), LiNi Z1 Mn 2-Z1 O4 (where 0 < Z1 < 2), etc.); lithium nickel cobalt-based oxides (such as LiNi 1-Y2 Co Y2 O2 (where 0 < Y2 < 1), etc.); lithium manganese cobalt-based oxides (such as LiCo 1-Y3 Mn Y3 O2 (where 0 < Y3 < 1), LiMn 2-Z2 Co z2O4 (where 0 < Z2 < 2, etc.); lithium nickel cobalt manganese-based oxides (e.g., Li(Ni P1 Co Q1 Mn R1 )O2 (where 0 < P1 < 1, 0 < Q1 < 1, 0 < R1 < 1, and P1 + Q1 + R1 = 1) or Li(Ni P2 Co Q2 Mn R2 )O4 (where 0 < P2 < 2, 0 < Q2 < 2, 0 < R2 < 2, and P2 + Q2 + R2 = 2), etc.); or lithium nickel cobalt manganese-other metal (M) oxides (e.g., Li(Ni P3 Co Q3 Mn R3 M 1 S )O2 (where M 1 is selected from the group consisting of aluminum (Al), copper (Cu), iron (Fe), vanadium (V), chromium (Cr), titanium (Ti), zirconium (Zr), zinc (Zn), tantalum (Ta), niobium (Nb), magnesium (Mg), boron (B), tungsten (W), and molybdenum (Mo), and P3, Q3, R3, and S are atomic fractions of each independent element, where 0 < P3 < 1, 0 < Q3 < 1, 0 < R3 < 1, 0 < S < 1, and P3 + Q3 + R3 + S = 1), etc.), and may include any one of them or a mixture of two or more.

[0041] The positive electrode active material may be included in an amount of 70% by weight to 99.5% by weight, preferably 80% by weight to 99% by weight, based on the total weight of the positive electrode active material layer. When the content of the positive electrode active material satisfies the above range, excellent energy density, positive electrode adhesion, and conductivity can be achieved.

[0042] The negative electrode may include a negative electrode active material layer. The negative electrode may further include a negative electrode current collector, and in this case, the negative electrode active material layer may be provided on one surface or both surfaces of the negative electrode current collector.

[0043] The negative electrode current collector is not particularly limited as long as the material of the negative electrode current collector has conductivity and does not cause adverse chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, their alloys, these materials surface-treated with carbon, nickel, titanium, silver, or the like, calcined carbon, etc. can be used.

[0044] The negative electrode current collector generally may have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the negative electrode current collector to improve the adhesion of the negative electrode active material. In addition, the negative electrode current collector may be used in various shapes such as a film, sheet, foil, net, porous body, foam body, non-woven fabric body, etc.

[0045] The negative electrode active material layer may include a negative electrode active material and a conductive agent.

[0046] The negative electrode active material may be a negative electrode active material commonly used in the art, and there is no particular limitation on its type.

[0047] The negative electrode active material may be, for example, at least one selected from the group consisting of carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; alloy powders of lithium and at least one metal selected from the group consisting of sodium, potassium, rubidium, cesium, francium, beryllium, magnesium, calcium, strontium, barium, radium, aluminum, germanium, and tin; silicon-based active materials such as Si, SiO v (O<v<2); tin-based active materials such as SnO2; lithium titanium oxide; and lithium metal powder. In some cases, the negative electrode active material may include a carbon coating on its surface.

[0048] The negative electrode active material may be included in an amount of 70% by weight to 99.5% by weight, preferably 80% by weight to 99% by weight, based on the total weight of the negative electrode active material layer. When the content of the negative electrode active material satisfies the above range, excellent energy density, electrode adhesion, and conductivity can be achieved.

[0049] The conductive agent may include a dot-shaped conductive agent and a carbon nanotube structure.

[0050] (1) Dot-shaped conductive agent

[0051] The dot-shaped conductive agent is used to be disposed between the electrode active materials, thereby forming a conduction path between adjacent electrode active materials.

[0052] The average particle diameter (D 50 ) of the dot-shaped conductive agent may be 1 nm to 500 nm, particularly 10 nm to 250 nm, and more particularly 20 nm to 200 nm. When the above range is satisfied, due to the high graphitization of the dot-shaped conductive agent, the conductivity of the electrode can be improved.

[0053] The dot-shaped conductive agent may include carbon black, and particularly may be carbon black. The carbon black may include at least one selected from the group consisting of acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black. The carbon black can be easily dispersed throughout the electrode to help uniform dispersion of electrons, thereby improving the conductivity of the electrode.

[0054] The dot-shaped conductive agent may be included in the electrode active material layer in an amount of 0.01% by weight to 5% by weight, particularly 0.01% by weight to 1% by weight, and more particularly 0.05% by weight to 0.5% by weight. When the above range is satisfied, the carbon black can be easily dispersed throughout the electrode to uniformly disperse electrons, thereby improving the conductivity of the electrode.

[0055] (2) Carbon nanotube structure

[0056] The carbon nanotube structure may include a plurality of single-walled carbon nanotube units. Specifically, the carbon nanotube structure may be a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other side by side. More specifically, in consideration of the durability and conductive network of the electrode, it is most preferred that the carbon nanotube structure is a carbon nanotube structure in which 2 to 4,500, preferably 50 to 4,000, and more preferably 1,000 to 4,000 single-walled carbon nanotube units are bonded to each other.

[0057] In the carbon nanotube structure, single-walled carbon nanotube units may be arranged side by side and combined (wherein the long axes of the units are combined parallel to each other to have a flexible cylindrical structure) to form a carbon nanotube structure. The carbon nanotube structure may be connected to each other to represent a network structure in an electrode.

[0058] Conventional electrodes including carbon nanotubes are generally prepared in the following manner: a bundle type or entangled type carbon nanotube (in the form of single-walled carbon nanotube units or multi-walled carbon nanotube units attached or entangled to each other) is dispersed in a dispersion medium to prepare a conductive agent dispersion, and then the conductive agent dispersion is used. In this case, the carbon nanotubes are completely dispersed in the conventional conductive agent dispersion, and exist in the form of a conductive agent dispersion in which carbon nanotube units in the form of single chains are dispersed. In the conventional conductive agent dispersion, the carbon nanotube unit is easily cut by an excessive dispersion process, so that the length of the carbon nanotube unit is shorter than the initial length. In addition, the carbon nanotube unit may be easily cut in the rolling process of the electrode, and another limitation is that the carbon nanotube unit (especially the single-walled carbon nanotube unit) is cut or its surface is damaged due to excessive changes in the volume of the electrode active material during battery operation. Therefore, due to the deterioration of the conductivity of the electrode, there is a limitation that the life characteristics of the battery are deteriorated. In addition, regarding the multi-walled carbon nanotube unit, the structure has high defects due to the node growth mechanism (not a smooth linear shape, but nodes exist due to defects generated during the growth process). Therefore, during the dispersion process, the multi-walled carbon nanotube unit is more easily cut (see Figure 1 (A)), and the short-cut multi-walled carbon nanotube units are likely to aggregate with each other via π-π stacking based on the carbon surface bonding structure (sp2) of the units. Therefore, it is difficult to make the multi-walled carbon nanotube units more uniformly dispersed and present in the electrode slurry.

[0059] Alternatively, regarding the carbon nanotube structure included in the electrode of the present invention, since the carbon nanotube structure is in the form of a rope in which 2 to 5,000 single-walled carbon nanotube units maintaining relatively high crystallinity without structural defects are arranged side by side and bonded to each other (see Figure 1 (B) and (C) and Figure 2 (A)), even if the volume of the electrode active material changes, the length of these single-walled carbon nanotube units can be well maintained without being cut, so the conductivity of the electrode can be maintained. In addition, since the high conductivity of the single-walled carbon nanotube unit with high crystallinity leads to an increase in the conductivity of the electrode, the resistance of the electrode can be reduced, the life characteristics of the battery can be improved, and the resistance of the battery can be reduced. In addition, since the carbon nanotube structure can be connected to each other and have a network structure in the electrode, the generation of cracks can be prevented by suppressing excessive changes in the volume of the electrode active material, and a strong conductive network can be ensured at the same time. In addition, even if cracks are generated in the electrode active material, the conductive network can be maintained because the carbon nanotube structure can connect the electrode active material while passing through the cracks. In addition, since the carbon nanotube structure is not easily damaged and can maintain its long shape, the conductive network can be enhanced throughout the electrode active material layer. In addition, the peeling of the electrode active material can be suppressed, thereby significantly improving the electrode adhesion. In addition, since the conductive agent content in the electrode can be reduced while ensuring the appropriate conductivity of the electrode, the energy density of the battery can be increased.

[0060] In particular, in view of the combined use with the point-type conductive agent, the point-type conductive agent is mainly arranged between the electrode active materials to form a conductive path between adjacent electrode active materials, thereby helping to ensure conductivity in a short length. In this regard, the carbon nanotube structure can help to ensure conductivity in a long length through a long length and a network structure. Therefore, a uniform conductive network can be formed in the entire electrode active material layer.

[0061] In the carbon nanotube structure, the average diameter of the single-walled carbon nanotube unit can be 0.5nm to 5nm, especially 1nm to 5nm. When the average diameter is met, even if a very small amount of conductive agent is used, there is an effect of maximizing the conductivity of the electrode. When the manufactured electrode is observed by TEM, the average diameter corresponds to the average value of the diameters of the first 100 single-walled carbon nanotube units with a larger average diameter and the last 100 single-walled carbon nanotube units with a smaller average diameter.

[0062] In the carbon nanotube structure, the average length of the single-walled carbon nanotube unit can be 1 μm to 100 μm, particularly 5 μm to 50 μm. When this average length is met, since a long conductive path for conductive connection between electrode active material particles can be formed and a unique network structure can be formed, even with a very small amount of conductive agent, there is an effect of maximizing the conductivity of the electrode. When the manufactured electrode is observed by TEM, the average length corresponds to the average of the lengths of the first 100 single-walled carbon nanotube units having a longer length and the last 100 single-walled carbon nanotube units having a shorter length.

[0063] The specific surface area of ​​a single-walled carbon nanotube unit can be 500m 2 / g to 1,000m 2 / g, especially 600m 2 / g to 800m 2 / g. When the above range is met, since the conductive path in the electrode can be smoothly ensured by a large specific surface area, even with a very small amount of conductive agent, there is an effect of maximizing the conductivity of the electrode. The specific surface area of ​​the single-walled carbon nanotube unit can be calculated by the nitrogen adsorption at liquid nitrogen temperature (77K) using Bell Japan's BELSORP-mini II.

[0064] The average diameter of the carbon nanotube structure can be 2nm to 200nm, particularly 5nm to 180nm, and more particularly 125nm to 170nm. When the above range is met, since it effectively forms a conductive network structure and is conducive to the connection between active material particles, excellent conductivity can be achieved. When the manufactured electrode is observed by SEM, the average diameter corresponds to the average value of the diameters of the first 100 carbon nanotube structures with larger diameters and the last 100 carbon nanotube structures with smaller diameters.

[0065] The average length of the carbon nanotube structure can be 1 μm to 500 μm, particularly 5 μm to 100 μm, and more particularly 15 μm to 35 μm. When the above range is met, excellent conductivity can be achieved because it effectively forms a conductive network structure and is conducive to the connection between active material particles. When the prepared electrode is observed by SEM, the average length corresponds to the average value of the lengths of the first 100 carbon nanotube structures with a larger average length and the last 100 carbon nanotube structures with a smaller average length.

[0066] The carbon nanotube structure can be included in the electrode active material layer in an amount of 0.01 wt % to 5 wt %, particularly 0.01 wt % to 0.5 wt %, and more particularly 0.01 wt % to 0.15 wt %. When the above range is met, since the conductive path of the electrode can be ensured, the life characteristics of the battery can be improved while the electrode resistance is kept at a low level. During the preparation of the conductive agent dispersion, the bundle-type carbon nanotubes are completely dispersed (as a general dispersion method, dispersion is performed to separate the single-chain carbon nanotube units from each other as much as possible), and the carbon nanotube structure will not be formed, or even if the carbon nanotube structure is formed inadvertently, only a very small amount (e.g., 0.0005 wt %) of the carbon nanotube structure will be formed. That is, the above-mentioned amount range may never be reached by a general method. Since the carbon nanotube structure has a form in which 2 to 5,000 single-walled carbon nanotube units are arranged side by side and combined with each other, even if the volume of the electrode active material changes, the carbon nanotube structure will not be cut and its length can be well maintained. Therefore, due to the high conductivity of the single-walled carbon nanotube unit, the conductivity of the electrode can be maintained and the conductivity of the electrode can be smoothly ensured. Therefore, even if the content of the carbon nanotube structure in the electrode is small, the life characteristics of the battery can be excellent.

[0067] In some cases, the single-walled carbon nanotube units may be surface treated by oxidation or nitridation to increase affinity with the dispersion.

[0068] The carbon nanotube structure may exist in the form of covering 50% or less, particularly 30% or less, and more particularly 20% or less of the surface of the electrode active material, for example, it may exist in the form of covering 10% to 20% of the area. If the carbon nanotube structure is coated on the electrode active material by a specific process, the carbon nanotube structure in the electrode active material layer may exist in a state of covering most of the surface of the electrode active material, and therefore the above range cannot be met. In the present invention, although the carbon nanotube structure is not combined with the electrode active material, an electrode slurry for preparing the electrode active material layer is formed, so the carbon nanotube structure can be uniformly distributed in the electrode active material layer. Therefore, since the phenomenon that most of the carbon nanotube structures cover the surface of the electrode active material is reduced, the carbon nanotube structure may exist in the form of covering 50% or less of the surface of the electrode active material. In addition, the carbon nanotube structure can smoothly build a conductive network in the electrode active material layer without being coated on the electrode active material layer because the conditions (e.g., mixing conditions, dispersant conditions, etc.) for preparing a dispersion containing the carbon nanotube structure are precisely adjusted, and thus a dispersion in which the carbon nanotube structure is well dispersed can be used. The above range can be confirmed by an image analysis program such as Amazon Rekognition or IX Image Analyzer.

[0069] The weight ratio of the point-type conductive agent to the carbon nanotube structure may be in the range of 9:1 to 1:9, particularly in the range of 8:2 to 2:8, and more particularly in the range of 7.8:2.2 to 2.2:7.8. In the case where the above range is satisfied, the output of the battery may be increased and its energy density may be higher. In addition, this may be optimal in terms of the dispersibility of the point-type conductive agent and the carbon nanotube structure.

[0070] The electrode active material layer may further include a binder. The binder is used to ensure the adhesion between the electrode active material particles or the adhesion between the electrode active material and the current collector, wherein the common binder used in the art can be used, and there is no particular restriction on its type. The binder may include, for example: polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, carboxymethyl cellulose (carboxymethyl cellulose: CMC), styrene-butadiene rubber (SBR), fluororubber or their various copolymers, and one of them can be used alone or a mixture of two or more of them can be used. When the binder includes polyvinylidene fluoride, the weight average molecular weight of the polyvinylidene fluoride used as a binder can be 800,000 g / mol or more, and particularly 800,000 g / mol to 1,000,000 g / mol.

[0071] The binder may be included in an amount of 10 wt % or less, and preferably 0.1 wt % to 5 wt % based on the total weight of the electrode active material layer. When the content of the binder satisfies the above range, excellent electrode adhesion can be achieved while minimizing the increase in the resistance of the electrode.

[0072] The electrode active material layer may include a dispersant. The dispersant may further include at least any one of polyvinylidene fluoride and carboxymethyl cellulose. Polyvinylidene fluoride and carboxymethyl cellulose help to disperse bundle-type or entangled single-walled carbon nanotubes in the conductive agent dispersion used in electrode manufacturing, and may be included in the electrode as the electrode slurry is prepared in the conductive material dispersion. Polyvinylidene fluoride may include modified polyvinylidene fluoride having an ester group, a carboxyl group, etc. on its surface, and in this case, the dispersion of the bundle-type carbon nanotubes may be further promoted.

[0073] The weight average molecular weight of the polyvinylidene fluoride that can be included as a dispersant can be 100,000 g / mol to 750,000 g / mol, particularly 400,000 g / mol to 700,000 g / mol. When the above range is met, the single-walled carbon nanotube units in the carbon nanotube structure can be firmly combined with each other while having a low viscosity, and at the same time, the carbon nanotube structure can be uniformly dispersed in the dispersion. Therefore, the conductivity of the electrode can be further improved.

[0074] Method for manufacturing electrode

[0075] Next, a method of manufacturing the electrode of the present invention will be described.

[0076] The method for manufacturing an electrode of the present invention may include the following steps: preparing a dot-type conductive agent dispersion and a carbon nanotube structure dispersion (S1); and forming an electrode slurry including the dot-type conductive agent dispersion, the carbon nanotube structure dispersion and an electrode active material (S2).

[0077] (1) Step (S1) for preparing dot-type conductive agent dispersion and carbon nanotube structure dispersion

[0078] 1) Preparation of dot-type conductive agent dispersion

[0079] After preparing a mixed solution containing the dot-type conductive agent of the above embodiment, a dispersion medium, and a dispersant, a dot-type conductive agent dispersion can be prepared by a method such as a homogenizer, a bead mill, a ball mill, a basket mill, a grinder, a universal stirrer, a transparent mixer, a pin mill, a TK mixer, and ultrasonic dispersion. The dispersion medium and the dispersant may be the same as those used in the preparation of the single-walled carbon nanotube unit dispersion to be described below, and thus will be described below.

[0080] 2) Preparation of carbon nanotube structure dispersion

[0081] The preparation of the carbon nanotube unit dispersion may include the following steps: preparing a mixed solution containing a dispersion medium, a dispersant, and bundle-type single-walled carbon nanotubes (bonded bodies or aggregates of single-walled carbon nanotubes) (S1-1); and dispersing the bundle-type single-walled carbon nanotubes by applying a shear force to the mixed solution, thereby forming a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded side by side (S1-2).

[0082] In step S1-1, a mixed solution can be prepared by adding bundled single-walled carbon nanotubes and a dispersant to a dispersion medium. In the bundled single-walled carbon nanotubes, the above-mentioned single-walled carbon nanotube units are combined to exist in the form of a bundle, wherein the bundled single-walled carbon nanotubes generally include 2 or more, substantially 500 or more, for example, 5,000 or more single-walled carbon nanotube units.

[0083] The specific surface area of ​​bundled single-walled carbon nanotubes can be 500m 2 / g to 1,000m 2 / g, especially 600m 2 / g to 800m 2 When the above range is satisfied, since a conductive path in the electrode can be smoothly ensured by a large specific surface area, the conductivity of the electrode can be maximized even with a very small amount of the conductive agent.

[0084] The bundle-type single-walled carbon nanotubes may be included in the mixed solution in an amount of 0.1 wt % to 1.0 wt %, for example, 0.2 wt % to 0.5 wt %. When the above range is satisfied, since the bundle-type single-walled carbon nanotubes are dispersed at an appropriate level, an appropriate level of carbon nanotube structure may be formed, and dispersion stability may be improved.

[0085] The dispersion medium may include, for example, an amide-based polar organic solvent such as dimethylformamide (DMF), diethylformamide, dimethylacetamide (DMAc) and N-methylpyrrolidone (NMP); an alcohol such as methanol, ethanol, 1-propanol, 2-propanol (isopropanol), 1-butanol (n-butanol), 2-methyl-1-propanol (isobutanol), 2-butanol (sec-butanol), 1-methyl-2-propanol (tert-butanol), pentanol, hexanol, heptanol or octanol; a glycol such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propylene glycol, 1,3-butanediol, 1,5-pentanediol or Hexylene glycol; polyhydric alcohols such as glycerol, trimethylolpropane, pentaerythritol or sorbitol; glycol ethers such as ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, tetraethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether or tetraethylene glycol monobutyl ether; ketones such as acetone, methyl ethyl ketone, methyl propyl ketone or cyclopentanone; esters such as ethyl acetate, γ-butyrolactone and ε-propiolactone, and any one of them or a mixture of two or more thereof can be used, but are not limited thereto. More specifically, the dispersion medium can be N-methylpyrrolidone (NMP).

[0086] The dispersant may include at least any one of polyvinylidene fluoride and carboxymethyl cellulose, and specifically polyvinylidene fluoride. Polyvinylidene fluoride may include modified polyvinylidene fluoride having an ester group, a carboxyl group, etc. on its surface, and in this case, the dispersion of the bundle-type carbon nanotubes may be further promoted.

[0087] The weight ratio of the bundle-type carbon nanotubes to the dispersant in the conductive agent dispersion may be in the range of 1:0.1 to 1:7, particularly 1:1 to 1:6. When the above range is satisfied, since the bundle-type single-walled carbon nanotubes are dispersed at an appropriate level, an appropriate level of carbon nanotube structure can be formed, and dispersion stability can be improved.

[0088] The solid content in the mixed solution may be in the range of 0.1 wt % to 20 wt %, particularly 1 wt % to 10 wt %. When the above range is satisfied, since the bundle-type single-walled carbon nanotubes are dispersed at an appropriate level, an appropriate level of carbon nanotube structure may be formed, and dispersion stability may be improved. In addition, the electrode slurry may have a viscosity and elasticity suitable for the electrode preparation process, and also contributes to increasing the solid content of the electrode slurry.

[0089] In step S1-2, the process of dispersing the bundle-type carbon nanotubes in the mixed solution can be performed by using a mixing device such as a homogenizer, a bead mill, a ball mill, a basket mill, a grinder, a universal stirrer, a transparent mixer, a pin mill, a TK mixer, or an ultrasonic (sonification) dispersion device. Among them, the beads mill method is preferred because the diameter size of the carbon nanotube structure can be controlled, the uniform distribution of the carbon nanotube structure can be achieved, and there is an advantage in cost.

[0090] The bead milling method may be as follows: The mixed solution is added to a container containing beads, and the container is rotated, thereby dispersing the bundled single-walled carbon nanotubes.

[0091] In this case, the conditions for performing the bead milling method are as follows.

[0092] The average diameter of the beads may be 0.5 mm to 1.5 mm, particularly 0.5 mm to 1.0 mm. When this range is satisfied, during the dispersion process, the carbon nanotube structure is not destroyed and the diameter of the carbon nanotube structure can be appropriately regulated, and a dispersion solution having a uniform composition can be prepared.

[0093] The rotation speed of the container may be 500 to 10,000 RPM, particularly 2,000 to 6,000 RPM. When this range is satisfied, during the dispersion process, the carbon nanotube structure is not destroyed and the diameter of the carbon nanotube structure can be appropriately regulated, and a dispersion solution having a uniform composition can be prepared.

[0094] The time for performing bead milling can be 0.5 hours to 2 hours, particularly 0.5 hours to 1.5 hours, and more particularly 0.8 hours to 1 hour. When this range is met, during the dispersion process, the carbon nanotube structure is not destroyed and the diameter of the carbon nanotube structure can be appropriately regulated, and a dispersed solution with a uniform composition can be prepared. The execution time of bead milling refers to the total time of using bead milling, for example, if bead milling is performed several times, the execution time refers to the total time spent for performing several bead millings.

[0095] The bead milling conditions are conditions for appropriately dispersing the bundled single-walled carbon nanotubes, and in particular, conditions that exclude the complete dispersion of the bundled single-walled carbon nanotubes into single-chain single-walled carbon nanotubes. That is, the bead milling conditions are conditions for appropriately dispersing the bundled single-walled carbon nanotubes to form a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bound side by side to each other in the prepared conductive agent dispersion. This can only be achieved when the composition of the mixed solution, the conditions of the dispersion process (e.g., the bead milling process), etc. are strictly controlled.

[0096] By means of the method, a carbon nanotube structure dispersion can be formed.

[0097] (2) Step (S2) for forming an electrode slurry including a dot-type conductive agent dispersion, a carbon nanotube structure dispersion, and an electrode active material

[0098] By the above method, when the dot-type conductive agent dispersion and the carbon nanotube structure dispersion are prepared, an electrode slurry including the dispersion and the electrode active material is formed. In this case, the above-mentioned electrode active material can be used as the electrode active material.

[0099] In addition, as needed, the electrode slurry may further include a binder and a solvent. In this case, the binder of the above embodiment may be used as a binder. The solvent may include, for example, dimethylformamide (DMF), diethylformamide, dimethylacetamide (DMAc) and N-methylpyrrolidone (NMP); alcohols such as methanol, ethanol, 1-propanol, 2-propanol (isopropanol), 1-butanol (n-butanol), 2-methyl-1-propanol (isobutanol), 2-butanol (sec-butanol), 1-methyl-2-propanol (tert-butanol), pentanol, hexanol, heptanol or octanol; glycols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propylene glycol, 1,3-butanediol, 1,5-pentanediol or hexanediol; polyhydric alcohols such as Such as glycerol, trimethylolpropane, pentaerythritol or sorbitol; glycol ethers, such as ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, tetraethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether or tetraethylene glycol monobutyl ether; ketones, such as acetone, methyl ethyl ketone, methyl propyl ketone or cyclopentanone; esters, such as ethyl acetate, γ-butyrolactone and ε-propiolactone, and any one of them or a mixture of two or more thereof can be used, but the present invention is not limited thereto. The solvent may be the same or different from the dispersion medium used in the pre-dispersion, and the solvent may preferably be N-methylpyrrolidone (NMP, N-methylpyrrolidone).

[0100] Next, the electrode slurry prepared as described above is dried to form an electrode active material layer. Specifically, the electrode active material layer can be formed by coating the electrode slurry on an electrode current collector and then drying the coated current collector, or can be formed by casting the electrode slurry on a separate carrier and then laminating the film separated from the carrier on the current collector. If necessary, after the electrode active material layer is formed by the above method, a rolling process can be further performed. In this case, taking into account the physical properties of the electrode finally prepared, drying and rolling can be performed under appropriate conditions, and there is no particular restriction.

[0101] Secondary battery

[0102] Next, a secondary battery according to another embodiment of the present invention will be described.

[0103] The secondary battery includes the electrode of the present invention as described above. In this case, the electrode may be at least one of a positive electrode and a negative electrode. Specifically, the secondary battery according to the present invention may include a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte, wherein at least one of the positive electrode and the negative electrode may be the above-mentioned electrode of the present invention, that is, an electrode including an electrode active material layer containing an electrode active material and a carbon nanotube structure. Preferably, the electrode of the present invention may be a positive electrode. Since the electrode according to the present invention has been described above, a detailed description will be omitted, and only other components will be described below.

[0104] The separator separates the negative electrode and the positive electrode and provides a mobile path for lithium ions, wherein any separator can be used as a separator, without particular limitation, as long as it is generally used for secondary batteries, and in particular, a separator having high moisture retention capacity for electrolytes and low resistance to the transmission of electrolyte ions can be used. Specifically, a porous polymer film can be used, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminated structure having two or more layers thereof can be used. In addition, conventional porous nonwoven fabrics can be used, for example, a nonwoven fabric formed by high melting point glass fiber or polyethylene terephthalate fiber. In addition, a coated separator including a ceramic component or a polymer component can be used to ensure heat resistance or mechanical strength, and a separator with a monolayer or multilayer structure can be selectively used.

[0105] The electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten-type inorganic electrolyte that can be used in the preparation of a lithium secondary battery, but is not limited thereto.

[0106] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.

[0107] For example, aprotic organic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran (franc), 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate can be used as the non-aqueous organic solvent.

[0108] Particularly, as the cyclic carbonate in the carbonate-based organic solvent, ethylene carbonate and propylene carbonate are well dissociated lithium salts in the electrolyte due to high dielectric constant as high viscosity organic solvents, so cyclic carbonate can be preferably used. Because when cyclic carbonate is mixed with low viscosity, the straight-chain carbonate of low dielectric constant such as dimethyl carbonate and diethyl carbonate in appropriate ratio, the electrolyte with high conductivity can be prepared, so cyclic carbonate can be more preferably used.

[0109] As the metal salt, a lithium salt can be used. The lithium salt is a material that is easily soluble in a non-aqueous electrolyte. For example, as an anion of the lithium salt, one selected from the group consisting of: F - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - .

[0110] In order to improve the life characteristics of the battery, suppress the reduction of the battery capacity, and improve the discharge capacity of the battery, in addition to the electrolyte components, at least one additive may be further included in the electrolyte, for example, a halogenated alkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum chloride.

[0111] According to another embodiment of the present invention, a battery module including the secondary battery as a unit cell and a battery pack including the battery module are provided. Since the battery module and the battery pack include secondary batteries having high capacity, high rate characteristics, and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0112] Hereinafter, the present invention will be described in more detail with reference to specific examples and comparative examples.

[0113] Preparation Example 1: Preparation of dot-type conductive agent dispersion

[0114] The specific surface area is 240m 2 / g of carbon black (diameter: 50 nm) and hydrogenated nitrile rubber (weight average molecular weight: 260,000 g / mol) were mixed with N-methylpyrrolidone (NMP) as a solvent to prepare a mixture having a solid content of 16.5 wt %.

[0115] The mixture was stirred by a beads-mill method, and the bundle-type carbon nanotubes were dispersed in a solvent to prepare a conductive agent dispersion. In this case, the diameter of the beads was 1 mm, the rotation speed of the stirring container containing the beads was 3,000 RPM, and stirring was performed for 60 minutes.

[0116] In the conductive agent dispersion, the amount of carbon black was 15 wt %, and the amount of hydrogenated nitrile rubber was 1.5 wt %.

[0117] Preparation Example 2: Preparation of Carbon Nanotube Structure Dispersion

[0118] Bundle-type single-walled carbon nanotubes (surface area 650 m2) composed of single-walled carbon nanotube units (average diameter 1.5 nm) 2 / g) and polyvinylidene fluoride (PVdF, KF9700, weight average molecular weight: 580,000 g / mol) were mixed in N-methylpyrrolidone (NMP) as a solvent to prepare a mixture having a solid content of 2.4 wt%.

[0119] The mixture was stirred by a bead mill method, thereby dispersing the bundle-type single-walled carbon nanotubes in the solvent, thereby preparing a carbon nanotube structure dispersion. In this case, the diameter of the beads was 1 mm, the rotation speed of the stirring container containing the beads was 3,000 RPM, and stirring was performed for 60 minutes. The carbon nanotube structure dispersion includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are combined side by side (see Figure 2 (A)).

[0120] In the carbon nanotube structure dispersion, the amount of the carbon nanotube structure was 0.4 wt %, and the amount of the polyvinylidene fluoride was 1.0 wt %.

[0121] Preparation Example 3: Preparation of Carbon Nanotube Structure Dispersion

[0122] In Preparation Example 2, polyvinylidene fluoride having a weight average molecular weight of 680,000 g / mol was used instead of polyvinylidene fluoride having a weight average molecular weight of 580,000 g / mol to prepare a carbon nanotube structure dispersion containing carbon nanotube structures having an average length of 20 μm.

[0123] Preparation Example 4: Preparation of Carbon Nanotube Structure Dispersion

[0124] In Preparation Example 2, polyvinylidene fluoride having a weight average molecular weight of 480,000 g / mol was used instead of polyvinylidene fluoride having a weight average molecular weight of 580,000 g / mol to prepare a carbon nanotube structure dispersion containing carbon nanotube structures having an average length of 5 μm.

[0125] Preparation Example 5: Preparation of single-walled carbon nanotube unit dispersion

[0126] The bundled single-walled carbon nanotubes (with a specific surface area of ​​650 m2) were composed of single-walled carbon nanotube units (with an average diameter of 1.5 nm). 2 / g) and hydrogenated nitrile rubber (weight average molecular weight: 260,000 g / mol) are mixed in N-methylpyrrolidone (NMP) as a solvent to prepare a mixture with a solid content of 4.4 wt% (the amount of bundle-type carbon nanotubes is 0.4 wt%, and the amount of hydrogenated nitrile rubber is 4.0 wt%).

[0127] The mixture was stirred by a bead mill method, thereby dispersing the bundle-type single-walled carbon nanotubes in the solvent, thereby preparing a conductive agent dispersion. In this case, the particle size of the beads was 1 mm, and the rotation speed of the stirring container containing the beads was 3,000 RPM. When one cycle was stirred for 60 minutes under the above conditions, a total of four cycles of stirring were performed (natural cooling for 60 minutes between each cycle). Thus, a single-walled carbon nanotube unit dispersion (see Figure 2 In the dispersion, the bundle-type single-walled carbon nanotubes were completely dispersed so that the single-walled carbon nanotube units existed in a single chain, and the above-mentioned carbon nanotube structure was not detected. In addition, in the single-walled carbon nanotube unit dispersion, the amount of the carbon nanotube structure was 0.4% by weight, and the amount of the hydrogenated nitrile rubber was 4.0% by weight.

[0128] Preparation Example 6: Preparation of Multi-walled Carbon Nanotube Unit Dispersion

[0129] The bundle-type multi-walled carbon nanotubes, hydrogenated nitrile rubber (H-NBR) as a dispersant, and N-methylpyrrolidone (NMP) as a dispersion medium were mixed in a weight ratio of 4:0.8:95.2 to form a mixture. The mixture was added to a pin mill in which 80% was filled with beads having a diameter of 0.65 mm, dispersed, and discharged at a discharge rate of 2 kg / min. This process was performed twice, and the bundle-type multi-walled carbon nanotubes were completely dispersed, thereby preparing a multi-walled carbon nanotube unit dispersion.

[0130] Examples and Comparative Examples

[0131] Example 1: Preparation of positive electrode

[0132] A positive electrode slurry was prepared, which included 3.91 wt % of the dot-type conductive agent of Preparation Example 1, 17.54 wt % of the carbon nanotube structure dispersion of Preparation Example 2, 68.62 wt % of LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), and 9.93 wt % of a binder (PVDF, weight average molecular weight: 900,000 g / mol), and including N-methylpyrrolidone (NMP) as a solvent. The positive electrode slurry was coated on a 20 μm thick aluminum (Al) thin film current collector (coated on both surfaces thereof), dried at 130° C., and then roll-pressed to prepare a positive electrode including a positive electrode active material layer.

[0133] In the positive electrode active material layer, LiNi 0.6 Co 0.2 Mn 0.2O2 (NCM622) is included in an amount of 97.6 weight %, the binder is included in an amount of 1.8 weight %, the binder is included in an amount of 0.1 weight %, the point type conductive agent is included in an amount of 0.3 weight %, the carbon nanotube structure is included in an amount of 0.1 weight %, and polyvinylidene fluoride as a dispersant is included in an amount of 0.1 weight %.

[0134] Reference Figure 3 , it can be seen that in the positive electrode of Example 1, the carbon nanotube structure in the form of a rope forms a network structure and connects the NCM622 to each other.

[0135] Example 2: Preparation of positive electrode

[0136] A positive electrode was manufactured in the same manner as in Example 1, except that the carbon nanotube structure dispersion of Preparation Example 3 was used instead of the carbon nanotube structure dispersion of Preparation Example 2 in Example 1.

[0137] Example 3: Preparation of positive electrode

[0138] A positive electrode was manufactured in the same manner as in Example 1, except that the carbon nanotube structure dispersion of Preparation Example 4 was used instead of the carbon nanotube structure dispersion of Preparation Example 2 in Example 1.

[0139] Example 4: Preparation of positive electrode

[0140] A positive electrode slurry was prepared, which included 11.5 wt % of the dot-type conductive agent of Preparation Example 1, 17.5 wt % of the carbon nanotube structure dispersion of Preparation Example 2, and 1.9 wt % of LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), and 9.1 wt % of a binder (PVDF, weight average molecular weight: 900,000 g / mol), and including N-methylpyrrolidone (NMP) as a solvent. The positive electrode slurry was coated on a 20 μm thick aluminum (Al) thin film current collector (coated on both surfaces thereof), dried at 130° C., and then roll-pressed to prepare a positive electrode including a positive electrode active material layer.

[0141] In the positive electrode active material layer, LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622) is included in an amount of 97.3 weight %, a binder is included in an amount of 1.2 weight %, a binder is included in an amount of 0.4 weight %, a point type conductive agent is included in an amount of 0.9 weight %, a carbon nanotube structure is included in an amount of 0.1 weight %, and polyvinylidene fluoride as a dispersant is included in an amount of 0.1 weight %.

[0142] Comparative Example 1: Preparation of positive electrode

[0143] A positive electrode was manufactured in the same manner as in Example 1, except that the carbon nanotube structure dispersion of Preparation Example 2 was not used and the dot-type conductive agent dispersion of Preparation Example 1 was used in the same amount as the carbon nanotube structure dispersion (only the dot-type conductive agent dispersion of Preparation Example 1 was used).

[0144] Comparative Example 2: Preparation of positive electrode

[0145] A positive electrode was manufactured in the same manner as in Example 1, except that the dot-type conductive agent dispersion of Preparation Example 1 was not used and the carbon nanotube structure dispersion of Preparation Example 2 was used in the same amount as the dot-type conductive agent dispersion (only the carbon nanotube structure dispersion of Preparation Example 2 was used).

[0146] Comparative Example 3: Preparation of positive electrode

[0147] A positive electrode was manufactured in the same manner as in Example 1, except that the single-walled carbon nanotube unit dispersion of Preparation Example 5 was used instead of the carbon nanotube structure dispersion of Preparation Example 1.

[0148] Comparative Example 4: Preparation of positive electrode

[0149] A positive electrode was manufactured in the same manner as in Example 1, except that the multi-walled carbon nanotube unit dispersion of Preparation Example 6 was used instead of the carbon nanotube structure dispersion of Preparation Example 2.

[0150] [Table 1]

[0151]

[0152] In the above-mentioned Examples 1, 4 and Comparative Example 2, the average diameter of the carbon nanotube structure (Preparation Example 2) was 100 nm and the average length was 10 μm. In the above-mentioned Example 2, the average diameter of the carbon nanotube structure (Preparation Example 3) was 150 nm and the average length was 20 μm. In the above-mentioned Example 3, the average diameter of the carbon nanotube structure (Preparation Example 4) was 50 nm and the average length was 5 μm.

[0153] In the above-mentioned Comparative Example 3, the single-walled carbon nanotube unit (Preparation Example 5) had an average diameter of 1.5 nm and an average length of 1 μm.

[0154] In the above-mentioned Comparative Example 4, the average diameter of the multi-walled carbon nanotube unit (Preparation Example 6) was 300 nm and the average length was 1.5 μm.

[0155] When the manufactured electrode is observed by TEM, the average diameter and the average length correspond to the average values ​​of the diameters and lengths of the first 100 carbon nanotube structures (or multi-walled carbon nanotube units, or single-walled carbon nanotube units) with larger diameters (or longer lengths) and the last 100 carbon nanotube structures (or multi-walled carbon nanotube units, or single-walled carbon nanotube units) with smaller diameters (or shorter lengths).

[0156] Test Example 1: SEM photo confirmation

[0157] The positive electrodes of Example 1 and Comparative Examples 1 to 3 were confirmed by SEM photographs. Figure 3 is a SEM photograph of the positive electrode of Example 1, Figure 4 is a SEM photograph of the positive electrode of Comparative Example 1. Figure 5 is a SEM photograph of the positive electrode of Comparative Example 2. Figure 6 This is a SEM photograph of the positive electrode of Comparative Example 3.

[0158] Reference Figure 3 , it can be seen that in the positive electrode of Example 1, a carbon nanotube structure in the form of a rope in which a plurality of single-walled carbon nanotube units are combined side by side with each other forms a network structure, and carbon black exists around the positive electrode active material and the carbon nanotube structure. At the same time, through the image analysis program, it can be confirmed that the carbon nanotube structure covers an area of ​​50% or less (about 20%) of the surface of the electrode active material.

[0159] Reference Figure 4 In the positive electrode of Comparative Example 1, no carbon nanotube structure was observed. Figure 5 In the positive electrode of Comparative Example 2, no carbon black (dot-type conductive agent) was observed. Figure 6 In the positive electrode of Comparative Example 3, only single-walled carbon nanotube units can be vaguely observed in a single chain, but no carbon nanotube structure is observed.

[0160] Test Example 2: Evaluation of battery energy density and capacity retention rate

[0161] Batteries were prepared as follows using the positive electrodes of Examples 1 to 3 and Comparative Examples 1 to 4, respectively.

[0162] The electrode assembly is formed by using a separator, 15 positive electrodes, 16 negative electrodes, and two single-sided positive electrodes, the difference between the single-sided positive electrode and the embodiment (or comparative example) is that the positive electrode active material layer is formed only on one surface of the collector. The positive electrode and the negative electrode are separated from each other by a separator, and the separator is located at each outermost portion of the electrode assembly. The negative electrode is in the form of each lithium metal stacked on both sides of a 10 μm thick copper foil collector with a thickness of 20 μm. The separator is in the form of Al2O3 and PVdF mixed in a weight ratio of 8:2 and coated on both sides of the polyethylene layer.

[0163] After that, the electrode assembly was placed in a case, and an electrolyte was added. Dimethyl carbonate (DMC) dissolved with 4M LiTFSI was used as the electrolyte.

[0164] Each lithium secondary battery was charged and discharged under the following conditions.

[0165] Charging conditions: Charge to 4.3V at 0.1C constant current

[0166] Discharge condition: Discharge to 2.8V at 0.1C constant current

[0167] When charging and discharging is one cycle, the discharge capacity after three cycles is regarded as the initial discharge capacity, as shown in Table 2.

[0168] Thereafter, the following cycle of changing the charge and discharge conditions was performed 50 times, and then the capacity retention ratio was evaluated. The results are shown in Table 2.

[0169] Charging conditions: 0.3C constant current charging to 4.3V

[0170] Discharge condition: Discharge to 2.8V at 2C constant current

[0171] The capacity retention rate refers to the ratio of the discharge capacity after 50 cycles to the initial discharge capacity of 100%. In addition, the energy density of the battery refers to the product of the initial discharge capacity (Ah) and the normal voltage (V) divided by the battery volume (L).

[0172] [Table 2]

[0173]

[0174] Test Example 3: Evaluation of battery output characteristics

[0175] An electrode assembly was formed in which two single-sided positive electrodes (otherwise the same as in the embodiment and the comparative example, but the positive electrode active material layer was formed only on one surface of the current collector) and one negative electrode were arranged as a separator / positive electrode / separator / negative electrode / separator / positive electrode / separator. The negative electrode was in the form of each lithium metal stacked on both sides of a 10 μm thick copper foil current collector at a thickness of 20 μm. The separator was in the form of Al2O3 and PVdF mixed in a weight ratio of 8:2 and coated on both sides of the polyethylene layer.

[0176] After that, the electrode assembly was placed in a case, and an electrolyte was added to prepare a battery. Dimethyl carbonate (DMC) in which 4M LiTFSI was dissolved was used as the electrolyte.

[0177] The battery was charged and discharged three times at a current of 0.33 C from 2.5 V to 4.2 V. Thereafter, 50% of the last third discharge capacity was discharged after charging to 4.2 V. Then, after standing for one hour, a current of 2.5 C was applied to reduce the voltage, and the resistance was calculated by the reduced voltage.

[0178] [Table 3]

[0179]

[0180] The following content corresponds to the original claims in the parent application and is now incorporated herein as part of the specification:

[0181] 1. An electrode comprising an electrode active material layer, the electrode active material layer comprising an electrode active material and a conductive agent, the conductive agent comprising a dot-type conductive agent; and a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other,

[0182] The average length of the carbon nanotube structure is 1 μm to 500 μm, and

[0183] The carbon nanotube structure is included in the electrode active material layer in an amount of 0.01 wt % to 5.0 wt %.

[0184] 2. The electrode according to item 1, wherein the weight ratio of the dot-type conductive agent to the carbon nanotube structure is 9:1 to 1:9.

[0185] 3. The electrode according to item 1, wherein the weight ratio of the dot-type conductive agent to the carbon nanotube structure is 8:2 to 2:8.

[0186] 4. The electrode according to item 1, wherein the dot-type conductive agent is included in the electrode active material layer in an amount of 0.01 wt % to 5 wt %.

[0187] 5. An electrode according to item 1, wherein the carbon nanotube structures are connected to each other to form a network structure in the electrode.

[0188] 6. The electrode according to item 1, wherein, in the carbon nanotube structure, the single-walled carbon nanotube units are arranged side by side and combined.

[0189] 7. The electrode according to item 1, wherein the average diameter of the carbon nanotube structure is 2 nm to 200 nm.

[0190] 8. An electrode according to item 1, wherein the average diameter of the carbon nanotube structure is 125 nm to 170 nm.

[0191] 9. The electrode according to item 1, wherein in the carbon nanotube structure, the average diameter of the single-walled carbon nanotube unit is 0.5 nm to 5 nm.

[0192] 10. The electrode according to item 1, wherein the average particle size (D 50 ) is 1nm to 500nm.

[0193] 11. An electrode according to item 1, wherein the dot-type conductive agent is carbon black.

[0194] 12. The electrode according to item 1, wherein the carbon nanotube structure is a carbon nanotube structure in which 50 to 4,000 single-walled carbon nanotube units are bonded to each other.

[0195] 13. An electrode according to item 1, wherein the carbon nanotube structure covers 50% or less of the surface area of ​​the electrode active material.

[0196] 14. A secondary battery comprising the electrode according to any one of items 1 to 13.

Claims

1. An electrode comprising an electrode active material layer, the electrode active material layer comprising an electrode active material and a conductive agent, the conductive agent comprising a dot-type conductive agent; and a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are arranged side by side and bonded to each other, The average length of the carbon nanotube structure is 1 μm to 500 μm. 2 . The electrode according to claim 1 , wherein a weight ratio of the dot-type conductive agent to the carbon nanotube structure is 9:1 to 1:

9. 3 . The electrode according to claim 1 , wherein a weight ratio of the dot-type conductive agent to the carbon nanotube structure is 8:2 to 2:

8. 4 . The electrode according to claim 1 , wherein the dot-type conductive agent is included in the electrode active material layer in an amount of 0.01 wt % to 5 wt %. The electrode according to claim 1 , wherein the carbon nanotube structures are connected to each other to form a network structure in the electrode. 6 . The electrode according to claim 1 , wherein the carbon nanotube structure has a cylindrical structure in which long axes of the units are coupled in parallel to each other to have flexibility. The electrode according to claim 1 , wherein the average diameter of the carbon nanotube structure is 2 nm to 200 nm. The electrode according to claim 1 , wherein the average diameter of the carbon nanotube structure is 125 nm to 170 nm.

9. The electrode according to claim 1, wherein In the carbon nanotube structure, the average diameter of the single-walled carbon nanotube unit is 0.5 nm to 5 nm.

10. The electrode according to claim 1, wherein the average particle size (D 50 ) is 1nm to 500nm.

11. The electrode according to claim 1, wherein the dot-type conductive agent is carbon black. 12 . The electrode according to claim 1 , wherein the carbon nanotube structure is a carbon nanotube structure in which 50 to 4,000 single-walled carbon nanotube units are bonded to each other.

13. The electrode according to claim 1, wherein the carbon nanotube structure covers 50% or less of the surface of the electrode active material. 14 . A secondary battery comprising the electrode according to claim 1 .

Citation Information

Patent Citations

  • Biopsy needle guide with pointer for simplified angle adjustment

    KR1020190123301A